ASSESSMENT OF MAGNETIC FIELD EXPOSURE AND CURRENT DENSITY FROM ELECTRICAL SUBSTATIONS IN POTISKUM METROPOLIS, YOBE STATE, NORTH-EAST, - A. D. BAJOGA; A. R. GARBA; H. SEYDOU; Y. HEBERT (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
This study was carried out to evaluate Extremely Low Frequency (ELF) Magnetic fields and associated current density across three (3) residential neighborhoods of electrical substations in Potiskum metropolis, with a view to assess the risk to public exposure among the residents. Three Hundred and Eighty-Four (384) data sets were collected 1 m above the ground using a Trifield meter facing four corners of the substations for each measurement at a radial distance of 3m, 6m, 9m and 12m away from the substations. The number of substations covered at each district are Potiskum West (6), Potiskum Central (10), and Potiskum Central (8), making a mean total of Twenty-Four (24) data sets. Data collected were evaluated using mathematical models given by Ahmad (2013), NIEHS (1998), ICNIRP (1998), Dong & Lu (2019), Canova et al. (2010), all assuming an ellipsoidal homogenous human body of isotropic conductivity at an EMF frequency of 50 Hz. The results indicate higher ELF magnetic field and current densities recorded at western, central and eastern districts are PWS3 (0.22 μT), PCS9 (0.45 μT) and PES3 (0.33 μT), respectively. Findings from the study show that the average exposure levels of ELF magnetic field in Potiskum central (0.30 μT) is higher compared to Potiskum West (0.17 μT) and Potiskum East (0.22 μT) residential sites. A strong positive correlation was also observed between the Magnetic field and current densities at all substations. Overall results shows that ELF magnetic field exposure and associated current densities were within the threshold of public exposure as recommended by ICNIRP guidelines.